2019
DOI: 10.1186/s13148-019-0763-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Dissecting the role of novel EZH2 inhibitors in primary glioblastoma cell cultures: effects on proliferation, epithelial-mesenchymal transition, migration, and on the pro-inflammatory phenotype

Abstract: BackgroundGlioblastoma (GBM) is the most lethal and aggressive malignant primary brain tumor in adults. After surgical resection of the tumor, the patient typically should be subjected to chemotherapy (temozolomide, TMZ) and concomitant radiotherapy. Since the TMZ treatment does not lead to complete remission and often develops resistance, the identification of efficacious therapeutics is strongly to pursue. Among the epigenetic players, the H3K27 methyltransferase (MT) EZH2 (enhancer of zeste homologue 2) has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 52 publications
0
53
0
Order By: Relevance
“…At present, the difficulty of multiple tumor treatments is the resistance of relapse and chemotherapy. Studies have pointed out that EMT signaling pathway is an important mechanism for the development of ovarian tumor [5,29]. Studies have shown that the BMP4-mediated signaling pathway led to morphological changes in tumor cells and enhanced cell adhesion, migration, and invasion by inducing EMT [30].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the difficulty of multiple tumor treatments is the resistance of relapse and chemotherapy. Studies have pointed out that EMT signaling pathway is an important mechanism for the development of ovarian tumor [5,29]. Studies have shown that the BMP4-mediated signaling pathway led to morphological changes in tumor cells and enhanced cell adhesion, migration, and invasion by inducing EMT [30].…”
Section: Discussionmentioning
confidence: 99%
“…Tazemetostat, an EZH2 inhibitor, has been approved for treating epithelioid sarcoma, and it is the first EZH2 inhibitor approved by FDA [47]. Other EZH2 inhibitor, GSK343 and GSK236, were also reported to inhibit tumor progression in various cancer, such as glioblastoma [48], head and neck cancer, [49] and breast cancer [50]. Our in vitro study confirmed the regulatory mechanism of miR-33a/EZH2 cascade in TNBC progression, thus, more investigation of the effects of miR-33a and EZH2 on tumor growth and metastasis in vivo is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The histone-lysine N-methyltransferase enzyme EZH2 (enhancer of zeste homolog 2), which catalyzes the addition of methyl groups to histone H3 at lysine 27 thereby silencing gene function, plays an important role in glioma progression. [64,65] EZH2 inhibitor GSK343 upregulates EZH2 target genes, leading to suppression of GBM growth and reversing PMT by controlling Ncadherin and vimentin expression. [66] Vinchure et al demonstrated that epigenetic control of miR-490-3p by EZH2 regulates PMT through TGIF2 signaling.…”
Section: Epigenetic Regulationmentioning
confidence: 99%